2018
DOI: 10.1186/s41938-017-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pheromone-binding proteins of the maize stem borer, Chilo partellus (Swinhoe, 1885) (Lepidoptera: Crambidae)

Abstract: Pheromone-binding proteins (PBPs) play a significant role in olfaction and mating. The present work was designed to isolate, extract, and purify the pheromone-binding proteins from the antennae of male Chilo partellus (Swinhoe, 1885) (Lepidoptera: Crambidae). The pheromone-binding proteins extracted from the male antennae were found to be 770 μg in 100 mg of sample. Pheromone-binding protein molecular weight was determined as 17 kDa by SDS-PAGE analysis. Identified proteins were purified through gel extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that dendrites that adjoining to the soluble PBPs/OBP in sensillum lymph were anticipated to relocate the dendrite membrane of the sensory neurons from the hydrophobic pheromone 22 . Other studies reported that PBPs attributed to certain receptions of sex-pheromone components, although PBPs were capable of binding to numerous pheromone components 22,25,5355 . This was because of the fact that the complex peripheral mechanism in the olfactory system possesses the ability to purify the selection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that dendrites that adjoining to the soluble PBPs/OBP in sensillum lymph were anticipated to relocate the dendrite membrane of the sensory neurons from the hydrophobic pheromone 22 . Other studies reported that PBPs attributed to certain receptions of sex-pheromone components, although PBPs were capable of binding to numerous pheromone components 22,25,5355 . This was because of the fact that the complex peripheral mechanism in the olfactory system possesses the ability to purify the selection.…”
Section: Discussionmentioning
confidence: 99%